VD_FINDINFO Arrêt / 2019 / 999 vom 25. Oktober 2019 - VD Tribunal cantonal (2019)
INSÉMINATION ARTIFICIELLE{ÊTRE HUMAIN}, CAS DE MALADIE | 25 al. 1 LAMal, 25 al. 2 let. a LAMal, 25 al. 2 let. b LAMal, 32 al. 1 LAMal, 3 LPGA